1997
DOI: 10.1177/036354659702500314
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Functional Knee Bracing on the Anterior Cruciate Ligament in the Weightbearing and Nonweightbearing Knee

Abstract: We investigated the effect of functional bracing on anterior cruciate ligament strain in humans by arthroscopic implantation of a differential variable reluctance transducer on the ligament and measurement of its strain behavior. Strains were measured while "injury mechanism" loads were applied to the weightbearing and nonweightbearing knees for both braced and unbraced conditions. For the unbraced knee, there was a significant increase in ligament strain values when subjects went from a seated position (minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 27 publications
0
86
0
2
Order By: Relevance
“…Modal analysis had conducted on four different layouts of knee brace in steel frame [7][8][9]. The five lowest order on natural vibration period of each scheme (T) was presented in Tab.1,and five lowest order on natural vibration period of each scheme was shown in Tab.…”
Section: A Results Of Modal Analysismentioning
confidence: 99%
“…Modal analysis had conducted on four different layouts of knee brace in steel frame [7][8][9]. The five lowest order on natural vibration period of each scheme (T) was presented in Tab.1,and five lowest order on natural vibration period of each scheme was shown in Tab.…”
Section: A Results Of Modal Analysismentioning
confidence: 99%
“…In contrast, Torzilli et al (1994) found anterior translation of the tibia in response to a joint compressive load (up to 444N), as did Oh et al (2011), who found translation coupled with internal rotation with a compressive load of 800N. These findings were corroborated in vivo: Beynnon et al (1997) and Fleming et al (2001) found an increase in ACL strain with the simple change from non-weight-bearing to weight-bearing. Weightbearing may increase ACL loading due to the posteroinferior slope of the proximal tibial surface (Hashemi et al, 2008) inducing an anterior shift on tibiofemoral compression (Fleming et al, 2001;Torzilli et al, 1994).…”
Section: Weight-bearingmentioning
confidence: 85%
“…Ligament strain (Ahmed et al, 1987;Bach & Hull, 1998;Berns et al, 1992;Beynnon et al, 1992;Beynnon et al, 1997;Fleming et al, 2001;Gabriel et al, 2004;Sakane et al, 1997;Takai et al, 1993;Torzilli et al, 1994) or load Markolf et al, 1995) increases with an anterior force on the tibia. When the ACL is cut anterior translation increases (Diermann et al, 2009;Fukubayashi et al, 1982;Hsieh & Walker, 1976;Markolf et al, 1976;Oh et al, 2011;Reuben et al, 1989;Wroble et al, 1993;Yoo et al, 2005;Zantop et al, 2007), or a given translation is resisted by a lesser force (Butler et al, 1980;Li et al, 1999;Lo et al, 2008;.…”
Section: Anterior Translationmentioning
confidence: 99%
“…6,19,30 Improved mechanical stability, decreased shear stresses, and protection against injury mechanisms have also been shown. 4,8,28 In addition to the protective function a brace can offer, neuromuscular and proprioceptive benefits have been observed in cutting activities, 6 gait, 11 and running. 43 Though early bracing has not demonstrated the long-term benefit commonly associated with a successful outcome, 8,28 protecting the knee against a catastrophic fall is intuitive and the development of position sense and neuromuscular control is a factor that contributes to the overall success of rehabilitation.…”
Section: Criteria For Progression and Goals Of Rehabilitation Followimentioning
confidence: 99%